Cross Cultural Adaptation and Cognitive Testing of a Psycho-Social-Spiritual Healing Measure, the NIH Healing Experiences in All Life Stressors-NIH-HEALS - Namisango, Eve; Luyirika, Emmanuel B. K.; Berger, Ann (Global advances in health and medicine, 2022)
Cancer is associated with trauma and stress which impacts the physical, psychological, and spiritual/existential well-being of patients. Psychological/behavioral healing may help alleviate this distress and the associated health-related suffering. Psycho-Social-Spiritual healing outcome measures are thus needed to stimulate service development. The NIH Healing Experiences in All Life Stressors (NIH-HEALS), is a novel 35-item measure of psycho-social-spiritual healing, developed in USA and is yet to be validated and adapted for use in African countries.This study aimed to assess the face and content validity of the NIH-HEALS in the population of cancer patients in Uganda and to culturally adapt this measure.Cross-sectional study using cognitive interviewing alongside standard piloting. We recruited adult (18 years and above) patients with advanced cancer from Hospice Africa Uganda. Interviews were conducted in two phases, using the think aloud technique and concurrent probing and were audio recorded. Phase 1 was used to identify initial concerns around clarity of the statements, and phase 2 further explored whether the issues of clarity had been addressed, alongside the standard cognitive interview parameters. The transcripts were imported into NVivo-12 analyzed using the content analysis technique and categorized using Tourengeau’s information processing model.We recruited thirty-five (35) patients: phase one (n = 5) two (n = 30). The median completion time was 20 minutes. Problems identified included comprehension of some statements, words, and phrases, suggestions to include local examples, highlighting of potentially sensitive statements that lean towards difficult conversations, and some cultural differences in the construction of the “Trust and Acceptance” construct, our sample showed less emphasis on family/friend relations. This feedback was used to adapt the NIH-HEALS for the local context.The NIH-HEALS has sufficient face and content validity properties to be used among palliative cancer patients in Uganda. We propose some changes to inform the adaptation of this measure for the local context.
Keywords: NIH healing experiences in all life stressors, psycho-social-spiritual healing, cross-cultural-use-Africa